Blood-debts and Battlefields: Ulster Imperialism and Masculine Authority on the Western Front 1916–1918 - McGaughey, Jane (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2009)
Men’s bodies were one of the more notable sites of conflict in Northern Ireland after the 1918 armistice. Long before the war was over, Ulstermen had become part of a public legacy of blood-sacrifice and the epic mythology of warrior manliness surrounding the 36th (Ulster) Division. The predominantly Protestant north-east of Ireland revelled in heroic language and romantic sentiment about their losses and the consequences of their sacrifice. For years after their most famous battle at the Somme on the 1st of July 1916, Unionists maintained a vibrant communal memory that pointedly excluded the achievements and sacrifices of the 16th (Irish) and 10th (Irish) Divisions, to the detriment of northern Nationalist veterans. More importantly, the ramifications of northern society’s understanding of soldiering masculinities directly led to some of the more infamous physical events of The Troubles from 1920 to 1922. These episodes included the violent shipyard expulsions in Belfast, the intimidation of shell-shocked ex-servicemen, membership in vigilante paramilitary societies, and government-mandated floggings of Catholic veterans in a society that prized service in the Great War as the greatest hallmark of modern Irish masculinity. The language of sacrifice within the public sphere, witnessed in public discourse and literally imprinted upon the bodies of those deemed unworthy and unmanly, mythologized one group of men at the expense of another, making the legacy of the Great War and the actions of and upon male bodies highly significant and influential factors in Northern Ireland for the rest of the twentieth century.